The role of information for the customer journey in mobile food ordering apps - Rita, Paulo (2022)
Rita, P., Eiriz, V., & Conde, B. (2022). The role of information for the customer journey in mobile food ordering apps. Journal Of Services Marketing. https://doi.org/10.1108/JSM-11-2021-0407 --- Funding: Paulo Rita was supported through the FCT (Fundação para a Ciência e a Tecnologia) under UIDB/04152/2020-Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.